Sex-Specific Microglial Activation and SARS-CoV-2 Receptor Expression Induced by Chronic Unpredictable Stress - Yan, Ling; Jayaram, Mohan; Chithanathan, Keerthana; Zharkovsky, Alexander; Tian, Li (Frontiers in Cellular Neuroscience, 2021)
Abstract The COVID-19 pandemic has generated a lot of stress and anxiety among not only infected patients but also general population across the globe, which disturbs cerebral immune homeostasis and potentially exacerbates the SARS-CoV-2 virus-induced neuroinflammation, especially among people susceptible for neuropsychiatric disorders. Here, we used a chronic unpredictable mild stress (CUMS) mouse model to study its effects on glia-mediated neuroinflammation and expressions of SARS-CoV2 viral receptors. We observed that female mice showed depressive-like behavior after CUMS, whereas male mice showed enhanced anxiety and social withdrawal. Interestingly, CUMS led to increased amounts of total and MHCII+ microglia in the hippocampi of female mice but not males. mRNA levels of SARS-CoV-2 viral receptors angiotensin-converting enzyme 2 (Ace2) and basigin (Bsg) were also upregulated in the prefrontal cortices of stressed females but not males. Similarly, sex-specific changes in SARS-CoV-2 viral receptors FURIN and neuropilin-1 (NRP1) were also observed in monocytes of human caregivers enduring chronic stress. Our findings provided evidence on detrimental effects of chronic stress on brain and behavior and implied potential sex-dependent susceptibility to SARS-CoV-2 infection after chronic stress.